2018
DOI: 10.26717/bjstr.2018.09.001861
|View full text |Cite
|
Sign up to set email alerts
|

Gallbladder Polyps Rarely Grow Beyond 10mm - Close Surveillance is Unnecessary for Polyps Smaller than 10mm

Abstract: Introduction: Small gallbladder polyps (GBP) are usually asymptomatic and benign and are monitored with regular ultrasonography (US) surveillance. Although most centers repeat imaging within a year, there remains no consensus regarding appropriate scan intervals.Aims: To investigate the size stability of GBP and to review the need for close surveillance.Methods: All abdominal ultrasound scans performed in our hospital over 3-month period were reviewed. Patients with sonographic evidence of GBP and with subsequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(8 citation statements)
references
References 22 publications
(41 reference statements)
1
7
0
Order By: Relevance
“…Our study adopted the ESGAR guidelines recommendation of ≥2 mm increase in GBP diameter as an indicator for 'true' GBP growth between two ultrasound examinations, 1 which found that only 8/100 (8%) of GBPs grew ≥ 2 mm in size over a mean follow-up period of 17.9 [AE 9.5] months. Similar findings where >85% of GBPs grew minimally at follow-up have been reported in one systematic review and two studies 6,26,27 : a systematic review found 5673/6100 (93%) of GBPs exhibited no growth or remained stable after a mean follow-up period of 51.5 (1-184) months. 6 A prospective study performed at the S. Orsola-Malpighi hospital in Italy found that 48/53 (91%) of GBPs did not change in size after a 5-year follow-up.…”
Section: Discussionsupporting
confidence: 84%
See 4 more Smart Citations
“…Our study adopted the ESGAR guidelines recommendation of ≥2 mm increase in GBP diameter as an indicator for 'true' GBP growth between two ultrasound examinations, 1 which found that only 8/100 (8%) of GBPs grew ≥ 2 mm in size over a mean follow-up period of 17.9 [AE 9.5] months. Similar findings where >85% of GBPs grew minimally at follow-up have been reported in one systematic review and two studies 6,26,27 : a systematic review found 5673/6100 (93%) of GBPs exhibited no growth or remained stable after a mean follow-up period of 51.5 (1-184) months. 6 A prospective study performed at the S. Orsola-Malpighi hospital in Italy found that 48/53 (91%) of GBPs did not change in size after a 5-year follow-up.…”
Section: Discussionsupporting
confidence: 84%
“…Firstly, it is likely that most GBPs detected in both study groups were cholesterol polyps, given that up to 80% of GBPs are typically cholesterol in origin. 1,6,7,26 Secondly, a systematic review found solitary GBPs had an increased malignancy risk by a factor of only 2.05 (P < 0.001) compared to multi-polyps, 1,6 while other studies have not found an associated significance on multivariate analysis. 1,9 As a result, the ESGAR guidelines stated there are no strong data to support a definitive association between solitary GBPs and malignancy risk.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations